Duplication, coclustering, and selection of human Alu retrotransposons - Jurka, Jerzy (National Academy of Sciences, 2004)
Alu and L1 are families of non-LTR retrotransposons representing ≈30% of the human genome. Genomic distributions of young Alu and L1 elements are quite similar, but over time, Alu densities in GC-rich DNA increase in comparison with L1 densities. Here we analyze two processes that may contribute to this phenomenon. First, DNA duplications in the human genome occur more frequently in Alu- and GC-rich than in AT-rich chromosomal regions. Second, most Alu elements tend to be coclustered with each other, but recently retroposed elements are likely to be inserted outside the existing clusters. These “stand-alone” elements appear to be rapidly eliminated from the genome. We also report that over time, the densities of recently retroposed Alu families on chromosome Y decline rapidly, whereas Alu densities on chromosome X increase relative to autosomal densities. We propose that these changes in the chromosomal proportions of Alu densities and the elimination of stand-alone Alus represent the same process of paternal Alu selection. We also propose that long-term Alu accumulation in GC-rich DNA is associated with DNA duplication initiated by elevated recombinogenic activities in Alu clusters.